Comparative Study: Use of Learning Languages in Mastering Printing Machine Operation Competencies (Case Study of Indonesian and Malaysian Printing Study Programs) - Amri, Lala Hucadinota Ainul (P3M Politeknik Negeri Media Kreatif, 2024)
The development of printing machines has undergone an extraordinary transformation along with advances in technology. One of the biggest advances in printing machine technology is the transition from traditional printing methods to digital printing. The production process becomes faster and more efficient. Today's printing machine technology is equipped with advanced features that improve print quality. Modern machines are equipped with intelligent control systems with operating language and instructions in English, human involvement in the production stage is absolute. This research uses descriptive qualitative analysis methods. The comparative study used two countries, Indonesia and Malaysia. As a result, Malaysian students who use English as the medium of instruction have the ability to understand printing machine operating instructions better than Indonesian students. Operating a printing machine has similar abilities to students from two countries. This study underscores the importance of integrating English into engineering curricula, with recommendations for improving Indonesian students' command of English.